PENERAPAN STRATEGI PEMBELAJARAN MIND MAP DALAM PENULISAN RESENSI BUKU PENGETAHUAN BERDASARKAN FORMAT BAKU PADA SISWA KELAS X A SMAK BONAVENTURA MADIUN TAHUN AJARAN 2015-2016 - Semi, Asteria; Adhani, Agnes (Educatio Vitae, 2017)
Class action research entitled “The Application of Mind Map Learning Strategy in Writing Textbook Review Based on Standard Form of X-A Students at Saint Bonaventura Senior High School Madiun, Academic Year of 2015-2016” is aimed to find out that the application of mind map learning strategy can raise the students’ activeness as well as their achievement in writing textbook review based on standard form. This research was done in two cycles which involved 23 students. It indicates that the students’ activeness during the first cycle of learning is in high or medium level. Here, it involved 12 students out of 23 students (65,22%). Meanwhile the students’ activeness during second cycle of learning is in the high and medium level. In this case, there were 23 students out of 23 students who participated (100%). Further, the percentage of students’ achievement in the first cycle of writing textbook review based on standard form is 65,22% or there were about 12 students completed it. For the second cycle, there were 23 students (100%) who completed it.